Brand-specific consumption of flavored alcoholic beverages among underage youth in the United States. (22nd November 2013) - Fortunato, Erin K.; Siegel, Michael; Ramirez, Rebecca L.; Ross, Craig; DeJong, William; Albers, Alison B.; Jernigan, David H.
Abstract: Background: Although several studies have identified flavored alcoholic beverages (FABs) as being popular among underage drinkers, no previous study has ascertained the prevalence of brand-specific FAB consumption among a national sample of underage youth. Objectives : To ascertain the brand-specific consumption prevalence and consumption share of FABs among a national sample of underage drinkers in the United States. Methods : In 2012, we conducted an online, self-administered survey of a national sample of 1031 underage drinkers, ages 13–20 years, to determine the prevalence of past 30-day consumption for each of 898 alcoholic beverage brands, including 62 FABs, and each brand's youth consumption share, based on the estimated total number of standard drinks consumed. There were three brand-specific outcome measures: prevalence of consumption, prevalence of consumption during heavy episodic drinking, and consumption share, defined as the percentage of the total drinks consumed by all respondents combined that was attributable to a particular brand. Results : The FAB brands with the highest prevalence of past 30-day consumption were Smirnoff malt beverages, 17.7%; Mike's, 10.8%; Bacardi malt beverages, 8.0%; and Four Loko/Four MaXed, 6.1%. Just five brands accounted for almost half (49.1%) of the total consumption share by volume within the FAB category. Conclusion : Flavored alcoholic beverages are highly popular among underage drinkers, and the FAB brand preferences of this group are highly concentrated among a small number of brands. To decrease the consumption of FABs by underage youth, all states should reclassify these beverages as distilled spirits rather than beer.